2015
DOI: 10.1002/jbio.201500006
|View full text |Cite
|
Sign up to set email alerts
|

Investigation on the potential of Mueller matrix imaging for digital staining

Abstract: Digital staining based on Mueller matrix measurements and their derivatives was investigated. Mueller matrix imaging was performed at the microscopic level on gastric tissue sections. Full Mueller matrices (4 × 4) were reconstructed using recorded images, followed by the extraction of polarization parameters. The most effective parameters and their combinations were extracted from Mueller matrix elements, principal component scores and polarization parameters respectively to classify samples into three categor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 31 publications
(17 citation statements)
references
References 36 publications
0
17
0
Order By: Relevance
“…A number of applications of Mueller polarimetric imaging are instead based on detecting unstained thin tissue cuts [22,131,144,[158][159][160][161][162] in a transmission geometry. Since Haematoxylin and Eosin (H&E) staining and other staining techniques require time and elaborate sample preparation by a well-trained and experienced pathologist for diagnosis, unstained Mueller microscopy may be used for rapid and low cost pathological inspection [159,160] and instant tissue characterization [136,163]. As shown in Figure 2(b), polarimetric imaging has been utilized to guide scanning mass spectroscopic analysis of a pathological slide of breast cancer tissue to detect suspicious cancerous regions.…”
Section: The Biomedical Applications Of Mueller-polarimetric Imagingmentioning
confidence: 99%
“…A number of applications of Mueller polarimetric imaging are instead based on detecting unstained thin tissue cuts [22,131,144,[158][159][160][161][162] in a transmission geometry. Since Haematoxylin and Eosin (H&E) staining and other staining techniques require time and elaborate sample preparation by a well-trained and experienced pathologist for diagnosis, unstained Mueller microscopy may be used for rapid and low cost pathological inspection [159,160] and instant tissue characterization [136,163]. As shown in Figure 2(b), polarimetric imaging has been utilized to guide scanning mass spectroscopic analysis of a pathological slide of breast cancer tissue to detect suspicious cancerous regions.…”
Section: The Biomedical Applications Of Mueller-polarimetric Imagingmentioning
confidence: 99%
“…Subsequent Wang et al 57 demonstrated the potential of polarimetry imaging for gastric tissue diagnosis at the microscopic level, whereby polarimetry was used to diagnose between normal gastric tissue, intestinal metaplasia, dysplasia and cancer, in a total of 84 samples for 59 patients. The accuracy of classification in digital staining using polarimetry imaging on the microscopic level varied from 56–75% for the discrimination of cancer, dysplasia and intestinal metaplasia or normal tissue.…”
Section: Emerging Technologiesmentioning
confidence: 99%
“…To circumvent this, chemical imaging techniques such as Fourier‐transform infrared spectroscopic imaging have been developed as a label‐free modality that utilize computerized algorithms to digitally recognize the biochemical composition of the underlying tissue structure (Mayerich et al ., ; Tiwari & Bhargava, ). In addition, recently researchers have also focused on developing digital staining methods to facilitate morphological assessment from images of unstained tissues (Bautista et al ., ; Amrania et al ., ; Wang et al ., ). In this paper, we introduce third‐harmonic generation (THG) imaging as a potential label‐free imaging technique to facilitate analysis of breast tumour tissue biopsies.…”
Section: Introductionmentioning
confidence: 97%